THU0030 Molecular mechanisms of autophagic memory in pathogenic t cells in human rheumatoid arthritis. (12th June 2018) - Kumar, P.; Leong, J.Y.; Saidin, S.; Paleja, B.; Loosdregt, J.V.; Chua, C.; Arkachaisri, T.; Consolaro, A.; Gattorno, M.; Martini, A.; Williams, G.W.; Pischel, K.D; et al.
Abstract : Background: One of the key elements of immune pathogenesis of human autoimmune arthritis is the resilience of pathogenic T cells. We have previously described that CD4 +T cells in patients with arthritis have an increased level of autophagy than their healthy equivalents. Here, we sought to explore at epigenetic and transcriptional levels the concept of persisting increased autophagy as the consequence of "autophagic memory", as one of the mechanisms conferring resilience to pathogenic T cells, in particular to a subset of CD4 +T cells (CPL: Circulating Pathogenic-like Lymphocytes), which are significantly more represented in patients with active arthritis and resistant to therapy with biologics Objectives: To understand molecular mechanism of resilience and persistence in pathogenic T cells in rheumatoid arthritis. Methods: Autophagy in T cells were analysed using CytoID autophagy detection kit. Jurkat cells pre-starved and control were harvested at various time points, and RNA was extracted for RNA-sequencing and DNA methylation analysis. Illumina paired end sequencing was performed and data was analysed using open source tools in R statistical programming software. CD4 +memory and naive T cells were sorted using flow cytometer for qPCR analysis. The CD4 +memory and naive cells were sorted using Flow cytometer. RNA extracted and converted to cDNA for qPCR analysis of key genes Results: First, we demonstrated elevated autophagic levels in CD4 +memory T cells when compared to naive CD4 +T cells. Second, we showed that autophagic levels are increased in naive and CD4 +T cells from RA patients compared to healthy controls. Using next generation RNA-sequencing, transcription factor gene regulatory network (TF-GRN) and methylation analyses, we identified MYC as key regulator of autophagic memory in a human T cell line. Transcriptome and network analysis of RNA-seq data from patients' CPLs confirmed MYC as key modulator of autophagy. Importantly, inhibitor of MYC increases autophagy Conclusions: The present study suggests that autophagic memory is retained both at the transcriptional and epigenetic levels as an integral part of mechanisms of efficient activation and survival of memory T cells. This mechanism is particularly relevant for cells subsets, such as CPLs, which are relevant to the immunopathogenesis of autoimmune diseases, such as arthritis. These studies have a direct translational valency as they identify autophagy and its metabolic controllers as a novel therapeutic target. Disclosure of Interest: None declared